Do ball-type attachment systems for overdenture result in better patient-satisfaction? A systematic review of randomized crossover clinical trial - Rosa, Cleber Davi Del Rei Daltro [UNESP]; de Souza Leão, Rafaella; Guerra, Cátia Maria Fonseca; Pellizzer, Eduardo Piza [UNESP]; Silva Casado, Bruno Gustavo da; Moraes, Sandra Lúcia Dantas de (Springer Nature, 2021)
Objective: This review is to compare patient-satisfaction with ball-type overdenture attachment systems with others attachment systems. Material and methods: This study was registered in PROSPERO (CRD42018097234) and adheres the PRISMA guidelines. Electronic searches on PubMed/MEDLINE, Scopus, Cochrane, and Web of Science databases for published articles were performed before October 2020. The PICO question was: “Do patients with a ball-type overdenture retention system have greater satisfaction, when compared to other attachment systems?” The evaluation of risk of bias was performed using the Cochrane risk of bias tool. Results: After searching the databases, seven articles were selected out of a total of 2583. A total of 312 implants were placed in 139 patients, with a mean age of 65.9 years. The risk of bias in the included studies varied according to the different domains in a risk of uncertain bias or low bias risk. No difference was found between the ball attachment systems and the others systems, with respect to patient-satisfaction. The meta-analysis revealed no statistically significant difference between the ball systems and another systems (P = 0.11; MD: 10.90; 95% CI: −2.55 to 24.35). Conclusions: Regarding patient general satisfaction, it was not possible to determine differences between the ball system and another types of attachment system for overdenture. The ball-type system was statistically superior only to the magnet system.
Keywords: Cross-over studies; Denture precision attachment; Overdenture; Patient-satisfaction; Prosthodontics; Systematic review